Accelerator and particle physics research for the next generation muon to electron conversion experiment - The PRISM task force - Pasternak,J; Jenner,LJ; Kurup,A; Uchida,Y; Muratori,B; Smith,SL; Hock,KM; Barlow,RJ; Ohmori,C; Witte,H; Yokoi,T; Lagrange,JB; et al. (2010)
The next generation of lepton flavour violation experiments will use high intensity and high quality muon beams. Such beams can be produced by sending a short proton pulse to the pion production target, capturing pions and performing RF phase rotation on the resulting muon beam in an FFAG ring, which was proposed for the PRISM project. A PRISM task force was created to address the accelerator and detector issues that need to be solved in order to realise the PRISM experiment. The parameters of the initial proton beam required and the PRISM experiment are reviewed. Alternative designs of the PRISM FFAG ring are presented and compared with the reference design. The ring injection/extraction system, matching with the solenoid channel and progress on the ring's main hardware systems like RF and kicker magnet are discussed. The progress and future directions of the study are presented in this paper.